Heart on the left, diaphragm on the right: A case of congenital diaphragmatic eventration. Issue 11 (22nd November 2021) - Naz, Sidra; Jaiswal, Vikash; Joshi, Amey; Jarullah, Furqan Ahmad; Jain, Esha; Neupane, Asmita
Abstract: Congenital Diaphragmatic Eventration (DE) requires a prompt diagnosis to avert the potentially life‐threatening complications. Herein, a 5‐month‐old male presented with recurrent respiratory infections due to a right‐sided diaphragmatic eventration. Misdiagnosed from previous medical visits, timely surgical intervention by thoracoscopic plication of the diaphragm was crucial for our patient's survival. Abstract : Diaphragmatic eventration (DE) is a life‐threatening abnormality that leads to one or both hemi‐diaphragms being elevated in the thoracic cavity. Congenital DE can fatally hinder lung formation. DE can be easily misdiagnosed, thus recognizing the presentation, and performing accurate interventions can allow for suitable management and favorable outcomes.